Application of different light sources for polymerization of restorative resins - Blažić Larisa; Živković Slavoljub; Stojšin Ivana (Serbian Medical Society - Dental Section, Belgrade, 2002)
The aim of this work was the introduction of the basic characteristics of contemporary polymerization light sources for composite resin curing. Two basic groups of available curing technologies are introduced. First are those that produce white light (conventional halogen lamps and plasma arc polymerization units). The second group comprises "blue light" curing devices that produce blue light at the origin of the light source. Lights belonging to this group include the blue LEDs and argon laser. Information about main characteristics of light sources (irradiance, wavelength range) and their proper choice could have a significant impact on polymerization quality and on long-life of composite restoration.